Efficient bioethanol production from sodium hydroxide pretreated corn stover and rice straw in the context of on-site cellulase production. (April 2018) - Zhao, Chen; Zou, Zongsheng; Li, Jisheng; Jia, Honglei; Liesche, Johannes; Chen, Shaolin; Fang, Hao
Abstract: A novel and efficient bioprocess from sodium hydroxide pretreated corn stover (SHPCS) or sodium hydroxide pretreated rice straw (SHPRS) to ethanol was successfully established, where the on-site cellulase production by the mixed culture of Trichoderma reesei and Aspergillus niger was used, producing 3.63 ± 0.35 FPIU/mL cellulase from SHPCS and 2.56 ± 0.33 FPIU/mL cellulase from SHPRS, respectively. Then those cellulases were applied to the enzymatic saccharification of SHPCS and SHPRS respectively, leading to yields of 81.5 ± 1.2% and 70.5 ± 2.1% respectively. Subsequently, SHPCS and SHPRS enzymatic hydrolysates mainly containing glucose and xylose were fermented by Saccharomyces cerevisiae, producing 27.6 ± 1.5 and 21.7 ± 1.9 g/L ethanol respectively. Concurrent with the distillation of fermentation broths for ethanol separation, the residual xylose was concentrated about 3 times. Thereafter, the distillation residues from SHPCS and SHPRS containing xylose were fermented by the adapted Pichia stipistis, producing 16.6 ± 1.1 and 13.0 ± 0.9 g/L ethanol respectively. In sum, the bioprocess could produce 33.1 g ethanol from 113.20 g SHPCS and 26.0 g ethanol from 117.58 g SHPRS. Highlights: A novel and efficient bioprocess from SHPCS or SHPRS to ethanol was established. Cellulase autarky was accomplished via on-site cellulase production by mixed culture. S. cerevisiae was the most robust in fermenting SHPCS or SHPRS enzymatic hydrolysate. The adapted P. stipistis was the most robust in fermenting the distillation residue.